Chapter 3 Plasma Concentration of Adipokines, Obstructive Sleep Apnea Syndrome and Chronic Kidney Disease in Patients with Metabolic Syndrome and Non-Alcoholic Fatty Liver Disease - Severova, Mariya; Saginova, Evgeniya; Galliamov, Marat; Ermakov, Nickolay; Rodina, Alla; Severov, Mikhail; Pulin, Andrey; Fomin, Viktor; Mukhin, Nikolay (IntechOpen, 2012)
None